Quantitative analysis of choroidal vascular structures and anatomical changes in pachychoroid spectrum diseases using ultra-widefield SS-OCTA - Bei Xiao; Yanping Song; Ming Yan; Ya Ye; Zhen Huang (Scientific Reports)
Abstract This study used ultra-widefield swept-source optical coherence tomography angiography (UWF SS-OCTA) to analyze and compare choroidal blood flow and anatomical changes in eyes affected by central serous chorioretinopathy (CSC), pachychoroid neovasculopathy (PNV), and uncomplicated pachychoroid (UCP). The findings revealed distribution patterns of vortex veins across the three patient groups and provided initial findings insights into the origin of choroidal neovascularization (CNV) in PNV. A total of 44 patients with CSC, 38 with PNV, and 46 with UCP were included in the analysis. Three-dimensional data were obtained from scans measuring 20 mm vertically by 24 mm horizontally with a scan depth of 6 mm, covering nine subfields. The results showed that CSC groups exhibited significantly higher choroidal vessel volume per unit area (mCVV/a), choroidal vascularity index (CVI), and choroidal thickness (CT) compared to the PNV and UCP groups. While the PNV and UCP groups shared similar choroidal vascular characteristics, the PNV group exhibited slightly higher choroidal vessel volume and notably the lowest foveal choriocapillaris density. These findings suggest that PNV and CSC may represent a continuous pathological spectrum, while UCP might be considered a precursor to CSC or a stage following its resolution. Additionally, further analysis indicated that CNV in PNV could be attributed to choriocapillaris occlusion and ischemia resulting from mechanical compression by hypertrophic choroidal vessels. These findings enhance our understanding of choroidal structure and hemodynamics within pachychoroid spectrum diseases (PSD), shedding light on shared etiological mechanisms and advancing the characterization of their pathophysiology.